Helping Undergraduates Generate Internship Opportunities Through Relationship Marketing: A Case Report - Belkora, Jeffrey K.; Koehne, Niklas (Frontiers in Education, 2021)
Undergraduate students often seek summer or academic-year internships as part of their academic and professional development. This case report illustrates a systematic self-marketing approach to generating internship opportunities, based on the theory of diffusion of innovations, and insights from the field of relationship marketing. Steps in the process for obtaining job or internship offers include: identifying areas of desired contribution; enlisting allies; identifying role models; interviewing role models; and demonstrating your value and joining the team. This case report illustrates how one student followed these steps to generate an internship opportunity. Overall, relationship marketing skills can help students improve their career prospects. Diverse students from under-resourced backgrounds may face barriers to accessing allies and role models. Such students should seek out pipeline programs that provide mentoring and other connections. These programs will improve student ability to engage in relationship marketing by expanding their network of allies, role models, and mentors. Employers should also identify pipeline programs and partner with them to assure greater inclusion of students from under-resourced backgrounds in their internship programs.